2001
DOI: 10.1021/bi002933d
|View full text |Cite
|
Sign up to set email alerts
|

The Antithrombin P1 Residue Is Important for Target Proteinase Specificity but Not for Heparin Activation of the Serpin. Characterization of P1 Antithrombin Variants with Altered Proteinase Specificity but Normal Heparin Activation

Abstract: Heparin has been proposed to conformationally activate the serpin, antithrombin, by making the reactive center loop P1 arginine residue accessible to proteinases. To evaluate this proposal, we determined the effect of mutating the P1 arginine on antithrombin's specificity for target and nontarget proteinases in both native and heparin-activated states of the serpin. As expected, mutation of the P1 arginine to tryptophan, histidine, leucine, and methionine converted the specificity of antithrombin from a trypsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
64
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 47 publications
10
64
0
Order By: Relevance
“…It has been postulated that the RCL of ATIII changes conformation upon binding H5 to a "canonical" conformation similar to that seen in the crystal structure of the related serpin, ␣ 1 -antitrypsin (8,7,40). Recent evidence suggests that although P1 Arg of ATIII may indeed reorientate upon binding H5, this alone does not explain the increased rate of interaction between the serpin and fXa (41,42).…”
Section: Discussionmentioning
confidence: 98%
“…It has been postulated that the RCL of ATIII changes conformation upon binding H5 to a "canonical" conformation similar to that seen in the crystal structure of the related serpin, ␣ 1 -antitrypsin (8,7,40). Recent evidence suggests that although P1 Arg of ATIII may indeed reorientate upon binding H5, this alone does not explain the increased rate of interaction between the serpin and fXa (41,42).…”
Section: Discussionmentioning
confidence: 98%
“…The N-terminal hinge residues of the antithrombin reactive loop are thus buried in ␤-sheet A in the free serpin structure but are expelled from sheet A in the heparin-complexed serpin, resulting in exposure of the loop in a manner typical of other serpin structures (21). Additionally, the x-ray structures together with biochemical and mutagenesis data have suggested that the primary specificity-determining residue of the loop, the P1 Arg-393 residue, makes a weak interaction with Glu-255 of the serpin body in the native partially buried loop conformation, which is then disrupted in the activated expelled loop state (22)(23)(24). However, mutagenesis of the reactive loop P6 -P3Ј residues that comprise the protease binding site has shown that conformational activation of antithrombin does not simply involve making the reactive loop more accessible to target proteases.…”
mentioning
confidence: 95%
“…However, mutagenesis of the reactive loop P6 -P3Ј residues that comprise the protease binding site has shown that conformational activation of antithrombin does not simply involve making the reactive loop more accessible to target proteases. Thus, whereas the reactivity of unactivated antithrombin with proteases is sensitive to such reactive loop mutations, the heparin enhancement in reactivity is not affected (5,22,25,26). These findings have suggested that exosites outside of the P6 -P3Ј reactive loop region are responsible for the heparin enhancement of antithrombin's reactivity with its target proteases.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…FVIIa can also be inhibited by the serpin (serine protease inhibitor) ATIII (antithrombin III), and the inhibition is accelerated many folds by sulfated glycosaminoglycans lining the vascular wall [4]. Interactions taking place at regions remote from the active-site cleft, at so-called exosites, also influence the rate of TFPI inhibition of the FVIIa-TF complex and FXa [5], whereas the direct interaction between ATIII and its target proteases is mediated primarily through active-site interactions and few exosite interactions [6].…”
Section: Introductionmentioning
confidence: 99%